Solving inverse nodal problem with frozen argument by using second Chebyshev wavelet method - Wang, Yu Ping; Kiasary, Shahrbanoo Akbarpoor; Yilmaz, Emrah (Springernature, 2024)
We consider the inverse nodal problem for Sturm-Liouville (S-L) equation with frozen argument. Asymptotic behaviours of eigenfunctions, nodal parameters are represented in two cases and numerical algorithms are produced to solve the given problems. Subsequently, solution of inverse nodal problem is calculated by the second Chebyshev wavelet method (SCW), accuracy and effectiveness of the method are shown in some numerical examples.
Keywords: Sturm-Liouville equation; inverse nodal problem; Frozen argument; nodal parameters; SCW method